Structural and compositional effect of heteropolyoxoanions [NiMo6-x WxO24H6]4- on the catalytic activity of clean selective oxidation of diphenylsulfide - Muñoz, Mercedes (2014)
Diphenyilsulfide oxidation by H2O2 as oxidant was studied through the structural effect of the isomorphous W-Mo systems, Anderson type, with [Ni(II)Mo(VI)6-xW(VI)xO24H6]4- composition. These phases were proved as alternative catalysts instead of W and Mo conventional systems. The characterization of the substituted phases was carried out by different physico-chemical techniques (AAS, DRS, micro-Raman, XRD, TPR). The catalytic evaluation for the phase NiW6 revealed that the process was selective to the sulfone formation (selectivity ~ 81-88 %) while the Ni-Mo bi-metallic system (NiMo6) was only selective to the sulfoxide production (selectivity 98 %). The activity was 90 % at 60 and 180 min for the NiMo6 and NiW6 respectively, whereas the substituted phases presented intermediate values. The observed differences can be related to the strength of the bridge bonds (Mo-O?Ni and W-O?Ni) associated to the higher electronegativity and ionic potential of Mo with respect to W. Hence, the W-O bond is more reactive by the inductive effect of Ni, which produces a higher oxidation of diphenyilsulfide to give sulfone, considering the electronic mobility in the redox processes.